Development of Tajwid Material Qalqalah Law Using Song at TPQ Al-Manar, Pabelan, Sukoharjo - Fauziah, Naila; Nurrohim, Ahmad; Diningrum, Melinda Retno (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This study aims to develop tajwid teaching materials, especially the law of qalqalah at TPQ al-Manaar located in Mendungan, Pabelan, Sukoharjo. This study began with analyzing the problems faced by students related to learning the Qur'an. The research and development process uses the ADDIE method (Analyze, Design, Develop, Implement, and Evaluate). The study's subjects were five students involved in the implementation or trial process. The research data were obtained by observing the students involved. The results of this study received a percentage of 75.7%, indicating that the song product containing the material of the law of qalqalah has met the criteria of valid, interesting, and effective. So, it can be concluded that the song containing the material of the law of qalqalah is suitable for use in tajwid learning for children at TPQ al-Manaar, Mendungan, Pabelan, Sukoharjo.